2023
DOI: 10.1177/10755470221151184
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Perspectives About COVID-19 and Vaccinations Among Native Americans

Abstract: The COVID-19 pandemic disproportionately affected Native American people and communities across the United States. Despite unequal losses during the pandemic, Native Americans have high vaccination rates. We provide insight into perspectives of COVID-19 and vaccinations through in-depth interviews with Native Americans. Through this research, we provide a holistic view of how Native Americans perceive vaccines by pairing Indigenous perspectives of risk and the Health Belief Model. We discuss the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…To assess whether our sample of vaccine hesitant/resistant individuals was consistent with previous literature ( 3 , 13–15 ), we first identified whether individuals were hesitant/resistant or not. Based on participants’ score on vaccine hesitancy (i.e., an average score higher than 3, the neutral point on the scale), participants were coded as vaccine hesitant/resistant (23%) or vaccine confident (77%).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…To assess whether our sample of vaccine hesitant/resistant individuals was consistent with previous literature ( 3 , 13–15 ), we first identified whether individuals were hesitant/resistant or not. Based on participants’ score on vaccine hesitancy (i.e., an average score higher than 3, the neutral point on the scale), participants were coded as vaccine hesitant/resistant (23%) or vaccine confident (77%).…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, several studies have been conducted to examine COVID-19 vaccine hesitancy in terms of worldwide rates of hesitancy, personal characteristics of hesitant individuals, and reasons for being hesitant [e.g., ( 3 , 13–15 )]. For example, drawing from large samples in Ireland and the United Kingdom (UK), Murphy et al ( 3 ) found that 35 and 31%, respectively, of these samples were vaccine hesitant/resistant.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research has explored the unique challenges NAs faced during the COVID-19 pandemic, including vaccine decision making among NAs living in urban [ 5 ] and reservation [ 6 ] settings, barriers to educational delivery [ 7 ], perceptions of COVID risk [ 8 ], testing [ 9 ], and impact on economic resources [ 10 ]. However, very limited research has focused on COVID-19 pandemic experiences among East Coast tribes [ 11 ], whose contexts and challenges may be different than tribes located within other US regions.…”
Section: Introductionmentioning
confidence: 99%